Sardar Vallabhbhai Patel and His Leading Role in Civil Disobedience Movement: The Contribution of Sardar Vallabhbhai Patel to the Civil Disobedience Movement in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Sardar Patel was a great leader of the Indian Sub-continent. His personality was constituted with the qualities of self-confidence, truthfulness and non-violence. He subsequently organized peasants from Kheda, Borsad and Bardoli in Gujrat in non-violent civil Disobedience against oppressive policies imposed by the British Raj.